Platelets Contribute to the Accumulation of Matrix Metalloproteinase Type 2 in Synovial Fluid in Osteoarthritis - Alunno, Alessia; Falcinelli, Emanuela; Luccioli, Filippo; Petito, Eleonora; Bartoloni, Elena; Momi, Stefania; Mirabelli, Giulia; Mancini, Giovanni B.; Gerli, Roberto; Gresele, Paolo (Thrombosis and Haemostasis, 2017)
Inflammation plays a role in the initiation and progression of osteoarthritis (OA), a chronic degenerative joint disorder. Platelets are inflammatory cells, contain and release matrix metalloproteinases (MMPs) and favour the release of these enzymes, key effectors of cartilage and subchondral bone degradation, by other cells; however, their role in OA has not been investigated yet. Our aims were (1) to assess the presence of platelets and of MMP-2 in synovial fluid (SF) of OA patients; (2) to evaluate the contribution of platelets to MMP-2 release by fibroblast-like synoviocytes (FLS); and (3) to investigate if hyaluronic acid (HA) interferes with these processes. SF was collected from 27 OA patients before and after treatment with intra-articular HA (20 mg/2 mL). Moreover, FLS were co-cultured with platelets, and the release of MMP-2 in supernatants was measured. Our results show that platelets are present in OA SF and show markers of activation. OA SF also contains relevant amounts of MMP-2. Co-incubation of platelets with FLS favours the release of MMP-2 by the interaction of platelet surface P-selectin with FLS CD44 by a mechanism involving the activation of pAkt and pSrc in FLS. Administration of HA to OA patients decreased the infiltration of platelets in SF and reduced the levels of MMP-2. The addition of HA in vitro inhibited the release of MMP-2 by FLS triggered by the interaction with platelets. In conclusion, our data show that platelets may contribute to joint degeneration in OA by favouring the accumulation of MMP-2 in SF.
Keywords: platelets; matrix metalloproteinases; synovial fluid; inflammation; hyaluronic acid